An undiagnosed giant right renal hydatid cyst treated laparoscopically: Case report and review of literature - Elsawi Osman (Urology Annals, 2016)
Hydatid disease caused by the tape worm Echinococcus granulosus is a rare occurrence in the urinary system in general. We are hereby presenting a case of a gentleman in his fourth decade with a giant right renal hydatid cyst. The clinical manifestations, radiological features, and serology were all not suggestive of hydatid disease; however, typical Echinococcus scolices were detected histologically following cyst aspiration. The giant cyst was successfully treated laparoscopically.